A systematic review: Unfinished nursing care and the impact on the nurse outcomes of job satisfaction, burnout, intention‐to‐leave and turnover - Stemmer, Renate; Bassi, Erika; Ezra, Sigal; Harvey, Clare; Jojo, Natasha; Meyer, Gabriele; Özsaban, Aysel; Paterson, Catherine; Shifaza, Fathimath; Turner, Murray B.; Bail, Kasia (Journal of advanced nursing, 2022)
Aim To investigate the association of unfinished nursing care on nurse outcomes. Design Systematic review in line with National Institute for Health and Care Excellence guideline. Data sources CINAHL, the Cochrane Library, Embase, Medline, ProQuest and Scopus databases were searched up until April 2020. Review Methods Two independent reviewers conducted each stage of the review process: screening eligibility, quality appraisal using Mixed Methods Appraisal Tool; and data extraction. Narrative synthesis compared measurements and outcomes. Results Nine hospital studies were included, and all but one were cross‐sectional multicentre studies with a variety of sampling sizes (136–4169 nurses). Studies had low internal validity implying a high risk of bias. There was also a high potential for bias due to non‐response. Only one study explicitly sought to examine nurse outcomes as a primary dependent variable, as most included nurse outcomes as mediating variables. Of the available data, unfinished nursing care was associated with: reduced job satisfaction (5/7 studies); burnout (1/3); and intention‐to‐leave (2/2). No association was found with turnover (2/2). Conclusion Unfinished nursing care remains a plausible mediator of negative nurse outcomes, but research is limited to single‐country studies and self‐reported outcome measures. Given challenges in the sector for nurse satisfaction, recruitment and retention, future research needs to focus on nurse outcomes as a specific aim of inquiry in relation to unfinished nursing care. Impact Unfinished nursing care has previously been demonstrated to be associated with staffing, education and work environments, with negative associations with patient outcomes (patient satisfaction, medication errors, infections, incidents and readmissions). This study offers new evidence that the impact of unfinished nursing care on nurses is under investigated. Policymakers can prioritize the funding of robust observational studies and quasi‐experimental studies with a primary aim to understand the impact of unfinished nursing care on nurse outcomes to better inform health workforce sustainability.